Multi‐therapies in androgenetic alopecia: review and clinical experiences. Issue 6 (18th July 2016) - Rossi, Alfredo; Anzalone, Alessia; Fortuna, Maria Caterina; Caro, Gemma; Garelli, Valentina; Pranteda, Giulia; Carlesimo, Marta
Abstract: Androgenetic alopecia (AGA) is a genetically determined progressive hair‐loss condition which represents the most common cause of hair loss in men. The use of the medical term androgenetic alopecia reflects current knowledge about the important role of androgens and genetic factors in its etiology. In addition to androgen‐dependent changes in the hair cycle, sustained microscopic follicular inflammation contributes to its onset. Furthermore, Prostaglandins have been demonstrated to have the ability in modulating hair follicle cycle; in particular, PGD2 inhibits hair growth while PGE2/F2a promote growth. Due to the progressive nature of AGA, the treatment should be started early and continued indefinitely, since the benefit will not be maintained upon ceasing therapy. To date, only two therapeutic agents have been approved by the Food and Drug Administration and European Medicines Agency for the treatment of AGA: topical minoxidil and oral finasteride. Considering the many pathogenetic mechanisms involved in AGA, various treatment options are available: topical and systemic drugs may be used and the choice depends on various factors including grading of AGA, patients' pathological conditions, practicability, costs and risks. So, the treatment for AGA should be based on personalized therapy and targeted at the different pathophysiological aspects of AGA.